Blunt major trauma: now two different diseases?. (2nd April 2020) - Coats, Timothy
Abstract : Major trauma in the UK has changed and can now be thought of as two different diseases: the traditional type of high energy transfer major trauma occurring in younger patients, and low energy transfer major trauma (usually an older person falling on one level). The current NHS trauma system is not well set up to treat low energy transfer major trauma – adapting to the changing disease is the next big challenge.